Determinación de reticulocitos y su relación con anemia en niños y preescolares que asisten a las guarderías del buen vivir del barrio Zamora Huayco y el Tejar de la Ciudad de Loja - Carrión Salcedo, Lucía del Cisne (2013)
The anemia is the decrease of the quantity of red blood cells in the blood or of the content of hemoglobin below the normal parameters; for its diagnosis there have been described several laboratory methods inside which it stands the Complete Blood Count (CBC) and the Reticulocyte Count that is used to evaluate the erythropoietic activity of the bone marrow. This was a descriptive and cross-sectional study applied in 103 preschooler children attending to the Good Living nurseries from Zamora Huayco and The Tejar neighborhoods of Loja’s city. This study was conducted in order to determinate the Reticulocyte Count, Hematocrit (Ht) and Hemoglobin (Hb), and the relationship between these values, obtaining the following results from the studied population: The 79.61% had a normal reticulocyte count, while the 20.39% had a low reticulocyte count; to determinate the Ht value it was concluded that the 49.51% had a low Ht value, and the 50.49% had normal values; the same way in the determination of the hemoglobin, it was found that the 66.02% had low values, and 33.98% had normal values; finally realating the values of hematocrit, hemoglobin and reticulocyte count, it was obtained that 4.85% had a low reticulocyte count with normal Hb, the 16.51% had a normal reticulocyte count with low Hb, and 78.64% had normal values of reticulocyte count and Hb; equally to relate the reticulocyte count with hematocrit, it was obtained that 5.83% had a low reticulocyte count with normal Ht, the 11.65% showed normal reticulocyte count with low Ht, and the 82.52% had normal values of reticulocyte count and Ht. KEY WORDS: Anemia, Complete Blood Count (CBC), reticulocyte count.